2011
DOI: 10.1371/journal.pone.0027617
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Defects in Hepatic Long Chain Fatty Acid Metabolism and Triglyceride Accumulation Contribute to Insulin Resistance in Non-Human Primates

Abstract: Non-Alcoholic fatty liver disease (NAFLD) is characterized by accumulation of triglycerides (TG) in hepatocytes, which may also trigger cirrhosis. The mechanisms of NAFLD are not fully understood, but insulin resistance has been proposed as a key determinant.AimsTo determine the TG content and long chain fatty acyl CoA composition profile in liver from obese non-diabetic insulin resistant (IR) and lean insulin sensitive (IS) baboons in relation with hepatic and peripheral insulin sensitivity.MethodsTwenty babo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 61 publications
3
26
0
Order By: Relevance
“…Plasma EC concentrations were measured at baseline, 3.5 wk, and 7 wk, whereas tissue concentrations were measured in biopsy samples taken at baseline and 7 wk. Liver biopsy samples were used to measure liver-TG content, as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma EC concentrations were measured at baseline, 3.5 wk, and 7 wk, whereas tissue concentrations were measured in biopsy samples taken at baseline and 7 wk. Liver biopsy samples were used to measure liver-TG content, as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…High fat diets (HFD) induce obesity and NAFLD [33,53,55,115,120,124]. However, despite the fact that NAFLD is more prevalent in women [23,24], most HFD-induced rodent models of NAFLD have focused only on males fed HFD ad libitum (rev.…”
Section: Introductionmentioning
confidence: 99%
“…These features distinguish baboons from rodents, which are frequently utilized in diabetes research (Chavez et al 2008). Previously we have shown that the adult baboon is a pertinent non-human primate model to examine the underlying cellular/molecular mechanisms responsible for insulin resistance, beta cell failure with islet of Langerhans remodeling and expansion of the glucagon cell component (Chavez et al 2008; Guardado et al 2009b; Guardado et al 2009a; Chavez et al 2009; Kamath et al 2011). Preterm baboons have significant gestational differences of key insulin signaling proteins in skeletal muscle, which may also contribute to neonatal hyperglycemia (Blanco et al 2010).…”
Section: Introductionmentioning
confidence: 99%